Diseases of the Teeth of Children Attending the Outpatient Department in the Dr. Pirngadi General Hospital Medan - Zakaria Siregar; Helena Siregar; Dachrul Aldy (Paediatrica Indonesiana, 1980)
Two surveys were conducted on children attending the Child Outpatient Department in the Dr. Pirngadi General Hospital Medan, to know about the spectrum and prevalence of the diseases of the teeth, and also the comparison of carious teeth formation between breastfed with bottlefed infant and children. The first survey was done in 1971 - 1973 on 18720 children, where 3000 (1 6.03%) of them had various dental diseases and abnormalities. We found that dental decay is prevailing at the age group of 3-8 years. The second survey was done in December 1977 on 100 children under five year of age, of whom 54 had caries while 46 of them had caries resembling bottlefeeding caries. No dental caries were found on children who got breastfeeding until the age of 41 months; bottlefeeding in infancy influences carious teeth formation.